2020
DOI: 10.1177/1203475420945234
|View full text |Cite
|
Sign up to set email alerts
|

Severe Acute Respiratory Syndrome Coronavirus 2 and the Use of Biologics in Patients With Psoriasis

Abstract: Coronavirus disease (COVID-19), a respiratory disease caused by a novel coronavirus designated severe acute respiratory syndrome coronavirus 2, has rapidly spread worldwide and has been recognized as a pandemic by the World Health Organization. Patients with altered immunologic function are at higher risk of acquiring COVID-19. In patients with psoriasis, inhibition of select pro-inflammatory cytokines through the use of biologic agents has been shown to be an effective treatment option. Pro-inflammatory cytok… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…For instance, some biologic agents for psoriasis inhibit pro-inflammatory cytokines and may potentially increase risk of infection, which further complicates treatment decisions during the COVID-19 pandemic. 16 Finally, communicating and collaborating on patient comanagement emerged as a challenge. This finding is particularly salient due to the complexity of distinguishing psoriasis symptoms from other diseases, the nature of symptoms presented to primary care, and the variety of treatments and their side effects, which often requires the involvement of specialists.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, some biologic agents for psoriasis inhibit pro-inflammatory cytokines and may potentially increase risk of infection, which further complicates treatment decisions during the COVID-19 pandemic. 16 Finally, communicating and collaborating on patient comanagement emerged as a challenge. This finding is particularly salient due to the complexity of distinguishing psoriasis symptoms from other diseases, the nature of symptoms presented to primary care, and the variety of treatments and their side effects, which often requires the involvement of specialists.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, some biologic agents for psoriasis inhibit pro-inflammatory cytokines and may potentially increase risk of infection, which further complicates treatment decisions during the COVID-19 pandemic. 16…”
Section: Discussionmentioning
confidence: 99%
“…The influence of biologics on respiratory tract infection susceptibility has recently been investigated. Higher risks of opportunistic infections and herpes zoster were reported among patients receiving immunosuppressive therapy to treat moderate-to-severe psoriasis [27]. TNF-α is expressed in the lung epithelial cells in response to respiratory viruses, such as influenza, and it recruits lympho-monocytes in the site of infection.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is inappropriate to speculate the susceptibility of SARS-CoV2 according to these previous studies because these studies did not analyze the risk of virus infection separately. More importantly, a published study suggested that the SARS, which has similar pathogenesis with SARS-CoV-2, may have a different immune response compared with other respiratory viruses ( 11 ). In the pandemic era, explaining the relationship between biologics and coronavirus infection is imperative.…”
Section: Introductionmentioning
confidence: 99%